Remarkable response to crizotinib in a patient with advanced lung adenocarcinoma harboring the MPRIP-ROS1 fusion gene: A case report - Yasuyuki Kishikawa; Kohei Otsubo; Daisuke Shibahara; Yoshimasa Shiraishi; Yasuto Yoneshima; Eiji Iwama; Isamu Okamoto (Respiratory Medicine Case Reports)
For patients with advanced non-small cell lung cancer (NSCLC), genetic testing is crucial to identify alterations in targetable driver genes. ROS1-tyrosine kinase inhibitors have shown efficacy against NSCLC with common ROS1 fusion genes, but the impact of rare fusion partners on therapeutic outcomes is not well understood. Here, we describe a 75-year-old female with advanced lung adenocarcinoma who was treated with crizotinib after the identification of the extremely rare MPRIP-ROS1 fusion. Despite stepwise dose reductions due to adverse effects, the patient exhibited a significant tumor response to crizotinib. The sustained response, even at reduced doses, highlights the potential for targeted therapies in managing NSCLC with MPRIP-ROS1 fusion. This case also underscores the importance of comprehensive genomic profiling using hybrid capture-based next-generation sequencing to identify rare driver gene alterations that may not be detected by conventional target sequencing-based methods.